The Use of DEAE Cellulose in the Preparation of a Factor VIII (AHG)-free Bovine Fibrinogen Reagent - Stapp, W. F (Thrombosis and Haemostasis, 1961)
Adequate fibrinogen reactivity is suggested as an additional requirement for specific fibrinogen reagents, to be added to the well known requirements of protein concentration, optimum pH, and optimum ionic strength. Reasons and a method for testing are outlined.A method for the preparation of a specific fibrinogen reagent, deficient in factor VIII, from BaSO4 adsorbed bovine plasma is described in detail. The method described utilizes either fresh or regenerated DEAE cellulose as an adsorbent in a non-column chromatographic adsorption procedure, associated with a dialysis procedure in which the final fibrinogen product is concentrated and precipitated as a “euglobulin”. The “euglobulin” fibrinogen precipitate was then dissolved/suspended in buffered saline at a specific pH and NaCl concentration. Essentially the method can be briefly outlined into 5 separate steps:1. Dialysis of BaSO4 adsorbed bovine plasma against 0.5% NaCl at pH 6.6 in 0.005 M Imidazole-HCl buffer.2. Washing of DEAE cellulose with the same type of buffered NaCl solution to specific conditions.3. Mixing of the dialyzed BaSO4 adsorbed bovine plasma with the washed DEAE cellulose and separation by centrifugation.4. Concentration of the cellulose adsorbed plasma as a “euglobulin” fibrinogen precipitate by dialysis against running tap water.5. Dissolving of the “euglobulin” fibrinogen precipitate in 0.9% NaCl buffered at pH 6.8.Fibrinogen preparations, prepared with the use of regenerated DEAE cellulose were found to be similar to those prepared by fresh DEAE cellulose in fibrinogen reactivity and deficiency in factor VIII activity, but were found to have less fibrinogen concentration than those prepared using fresh DEAE cellulose.Suggestions were also made for possibly increasing the over-all yield of the fibrinogen reagent through use of a “washing-elution” procedure.The procedure that was used for regenerating the DEAE cellulose was also described in detail and commented upon.